An Analytical Study of NPA and its Affect in Purvanchal & Sarva U.P. Gramin Bank - Shrivastava, Aman; Banerjee, Sudip (Journal of Advanced Research in Humanities and Social Sciences; Vol 9 No 2 (2022): Journal of Advanced Research in Humanities and Social Sciences, 2022)
Indian Economy heavily depends on Banking Sector. Rural Banking provide finance in semi urban and rural areas. Due to growing NPAs in the banks, the Indian banking system is currently facing numerous difficulties. This paper focusing on the Regional Rural Banks of Uttar Pradesh. Two banks selected for this research Purvanchal Bank and Sarva U.P Graim Bank both these banks are functioning in Eastern Uttar Pradesh which is underdeveloped when it compare to Western Uttar Pradesh. Due to lack of industrialization these area a large number of people are staying in Rural Areas so these two banks are functional in rural areas. This research will study the bank businesses, profitability and NPAs of these banks from the period of 2013-2018. How to cite this article: Jain J, Banerjee S. An Analytical Study of NPA and its Affect in Purvanchal & Sarva U.P. Gramin Bank. J Adv Res Humani Social Sci 2022; 9(2): 8-16.